JMJ Histone Demethylases Balance H3K27me3 and H3K4me3 Levels at the HSP21 Locus during Heat Acclimation in Arabidopsis - Yamaguchi, Nobutoshi (Biomolecules, 2021)
Exposure to moderately high temperature enables plants to acquire thermotolerance to high temperatures that might otherwise be lethal. In Arabidopsis thaliana, histone H3 lysine 27 trimethylation (H3K27me3) at the heat shock protein 17.6C (HSP17.6C) and HSP22 loci is removed by Jumonji C domain-containing protein (JMJ) histone demethylases, thus allowing the plant to ‘remember’ the heat experience. Other heat memory genes, such as HSP21, are downregulated in acclimatized jmj quadruple mutants compared to the wild type, but how those genes are regulated remains uncharacterized. Here, we show that histone H3 lysine 4 trimethylation (H3K4me3) at HSP21 was maintained at high levels for at least three days in response to heat. This heat-dependent H3K4me3 accumulation was compromised in the acclimatized jmj quadruple mutant as compared to the acclimatized wild type. JMJ30 directly bound to the HSP21 locus in response to heat and coordinated H3K27me3 and H3K4me3 levels under standard and fluctuating conditions. Our results suggest that JMJs mediate the balance between H3K27me3 and H3K4me3 at the HSP21 locus through proper maintenance of H3K27me3 removal during heat acclimation.